(untitled) (Research, Society and Development, 2022)
Prodigiosin is a microbial red pigment, mainly produced by the bacterium Serratia marcescens, considered as a promising antimicrobial, immunosuppressive and antiproliferative compound. However, its industrial commercialization is still limited because of the high cost of production mainly due to the use of expensive substrates. Hence, this work aimed to the sustainable production of prodigiosin by S. marcescens UCP 1549, using corn bran as alternative and low-cost substrate, and its application in soap coloring. According to the results, both bacterial growth and red pigment production occurred, achieving 7.24 g/L and 1.68 g/L of biomass and pigment yield, respectively. Positive result in the presumptive test indicated red pigment as prodigiosin, which was confirmed by UV-Visible spectrophotometry (maximum absorbance peak at 535 nm), TLC (Rf 0.9) and the functional groups identified by FTIR spectroscopy. Prodigiosin showed color stability at different pH values and NaCl concentration. The application of pigment in soap coloring was effective, suggesting its promising potential in the cosmetics industry as natural colorant. The results showed the biotechnological potential of S. marcescens UCP 1549 in the biotransformation of corn bran into prodigiosin, allowing a more economically and competitively industrial bioprocess.